Kościół wobec pamięci zbiorowej polskiego społeczeństwa. O niektórych strategiach i celach „kościelnej polityki pamięci”. - Stachowiak, Paweł (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The author observes that the objectives of the Church’s remembrance policy also have a more earthly dimension. This concerns the defense of the Church’s position in public life and preventing attempts to marginalize the Church. By means of conducting its own remembrance policy the Church intends to augment the monumental aspect of collective Polish memory seeing it as an opportunity to maintain the most extensive range of influence.